Safety issues improvement in ceramic lined composite pipe produced using SHS method - Mahmoodian, Reza; Rahbari, Reza; Abd Shukor, Mohd Hamdi (2011)
Self-Propagating High-Temperature Synthesis (SHS) or combustion synthesis (CS) is an advanced method for producing high temperature materials such as refractory materials, intermetallics, and cermets. Combustion synthesis is characterized by extremely heating rate, high temperatures, and short reaction times. Centrifugal force densification was employing to produce dense ceramic-lined steel pipes. The centrifugal force facilitates phase separation of multi-component products during the process. In this research the safety matters in producing ceramic lined composite pipes from Fe2O3 – Al powder mixture is studied. A SHS centrifugal machine with the acceleration up to a = 350g was developed. Thermite reaction of Fe2O3 and Al was occurred inside the pipe to produce Al2O3 ceramic in the innermost layer and Fe layer at a region between the outer steel pipe and the ceramic layer.